Urban stream: Level of disturbance and water quality - Luana Urata , Stephanie; Eduarda Aranega Pesenti , Maria; Belchor de Lara , Beatrice; Andrade Marques , Thiago; Valeria Marques Cardoso Prates, Kátia (Seven Editora, 2023)
The growth of urban centers has been causing interference in water quality. Because of this, it is necessary to monitor the environment of water bodies, either by quality parameters or by the application of the Rapid Assessment Protocol (PAR). In this context, this study aimed to evaluate the level of disturbance and water quality of the Água Fresca Stream, a microbasin of the Cambé stream in the municipality of Londrina, in the north of Paraná, by means of a PAR and physicochemical analyses of turbidity, electrical conductivity and pH, and microbiological analyses of heterotrophic bacteria, total coliforms and Escherechia coli (E.coli). For this, five sampling points were established and water collection campaigns were carried out in two months with different rainfall rates, being March (215.1 mm) and April (83.6 mm) of 2022. From the analysis of the PAR it is concluded that the Água Fresca Stream can be considered as an impacted stretch, also observed by the values of electrical conductivity, from 161 to 173 μS/cm. The highest concentrations of total coliforms, heterotrophic bacteria and E.coli occurred in the month with the highest rainfall, reaching concentrations of 62,600, 163,900 and 3,000 CFU/100 mL, respectively, influenced by the greater surface runoff caused by rainwater. DOI: https://doi.org/10.56238/Connexpemultidisdevolpfut-081